Fufang Zhenzhu Tiaozhi Capsule Prevents Intestinal Inflammation and Barrier Disruption in Mice With Non-Alcoholic Steatohepatitis - Tian Lan; Tian Lan; Tian Lan; Tian Lan; Tonghao Xu; Tonghao Xu; Tonghao Xu; Tonghao Xu; Yanfang Fu; Yanfang Fu; Yanfang Fu; Yanfang Fu; et al. (Frontiers in Endocrinology, 2022)
Nonalcoholic steatohepatitis (NASH) has become a major cause of liver transplantation and liver-associated death. Targeting the gut–liver axis is a potential therapy for NASH. The Fufang Zhenzhu Tiaozhi (FTZ) capsule, a traditional Chinese medicine commonly used in clinical practice, has recently emerged as a promising drug candidate for metabolic diseases such as NASH. The present study aimed to investigate whether FTZ exerts an anti-NASH effect by targeting the gut–liver axis. Mice were fed with a high-fat diet (HFD) for 20 weeks to induce NASH. HFD-fed mice were daily intragastrically administrated with FTZ at 10 weeks after tbe initiation of HFD feeding. The mRNA levels of genes associated with the intestinal tight junction, lipid metabolism, and inflammation were determined by the q-PCR assay. Hepatic pathology was evaluated by H&E staining. The gut microbiota was analyzed by 16S rRNA gene sequencing. FTZ attenuated HFD-induced obesity, insulin resistance, and hepatic steatosis in mice. FTZ treatment decreased the elevated levels of serum aminotransferases and liver triglyceride in NASH mice. Furthermore, FTZ treatment reduced hepatic inflammatory cell infiltration and fibrosis in mice. In addition, FTZ attenuated the intestinal inflammatory response and improved intestinal barrier function. Mechanistically, FTZ-treated mice showed a different gut microbiota composition compared with that in HFD-fed mice. Finally, we identified eight differential metabolites that may contribute to the improvement of NASH with FTZ treatment. In summary, FTZ ameliorates NASH by inhibiting gut inflammation, improving intestinal barrier function, and modulating intestinal microbiota composition.